ANALASIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 28/PUU-XI/2013 TENTANG UJI MATERI ATAS UNDANG-UNDANG NOMOR 17 TAHUN 2012 TENTANG PERKOPERASIAN - OKTO BERLIN GULTOM (PREMISE LAW JURNAL, 2015)
Cooperative Law No. 17/2012 is the last law on cooperative legalized by the Legislative Assembly. The law is legalized on 30 October 2012 as the Substitute of Cooperative Law No.25/1992. Cooperative Law No. 17/2012 is reviewed judicially by six cooperatives and two individuals. Judge of the Constitutional Court in the decision stated Cooperative Law No.17 is invalid. Due to the decision, Cooperative Law No. 25/1992 is valid as Cooperative Law for temporary until a new cooperative law is legalized. By the cancelation of Cooperative Law No. 17/2012, the law cannnot be used as the basis of cooperative in Indonesia. The status of the cooperative management that are not from the cooperative members after the decision of Constitutional Court No. 28/PUU-XI/2013 do not have the right to be the cooperative management because the Cooperative Law No. 25/1992 that becomes the temporary Cooperative Law states that management can be choosen from the cooperative members. Government should really make a cooperative regulation for the improvement of cooperative and not only for the interest of government. Cooperative members should be the pole to improve the potentials possessed so that cooperative members that will become the management improve the cooperative in the future. Keywords: Judicial Analysis, Decision of Constitutional Court, Cooperative